National Elections and the Autonomy of American State Party Systems - Gimpel, James G. (University of Pittsburgh Press, 1996)
Traditional theories of party organization have emphasized two-party electoral competition as the force behind party unity in state politics. V. O. Key first advanced this theory in Southern Politics, where he concluded that party factionalism in the South was mainly attributable to the one-party character of the region. But this traditional theory does not fit all states equally well. In the states of the West, especially, parties are competitive, but politic.